Self-Regulation and Mobile Phone Involvement Among Islamic University Students - Melisa Paulina; Linda Utami; Lisneni Dewi; Eva Masita Adnan (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2026)
As Generation Z, born digital natives, students these days seem inseparable from their phones, even in the classroom. To some extent, this is certainly distracting. This study investigates the relationship between self-regulation and mobile phone involvement among Islamic university students. The rapid proliferation of mobile phone and mobile phone involvement among students has raised concerns about its psychosocial, academic, and spiritual consequences, particularly regarding the effectiveness of religious values as an internal control mechanism. Therefore, this research focuses on whether self-regulation influences mobile phone involvement in this population. Employing a quantitative correlational design, the study involved 446 Islamic University Students as participants. Data were analyzed using simple linear regression. Results indicate that the relationship between self-regulation and mobile phone involvement is not statistically significant. These findings suggest that self-regulation does not significantly affect the level of mobile phone involvement among Islamic University Students. This study contributes to the literature on Islamic psychology and education and recommends interventions rooted in contextual religious values to enhance Islamic University Students’ self-control capacities in the digital age.